PENGARUH INFLASI, SUKU BUNGA, EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER) DAN PRICE TO BOOK VALUE (PBV) TERHADAP HARGA SAHAM PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B11111002, VINA YUNITA (Jurnal Manajemen Update, 2015)
Capital markets as a way for investors to invest their funds to various sectors of the company that are considered to have good prospects. One form of investment favored by investors is investing stock. The investors who will purchase shares in capital market will do various analyzes both the internal factors and external factors before taking any investment decisions. This is intended that the investments can give  profit to investors. Therefore, this study aimed to analyze the effects of inflation, interest rates, Earning Per Share (EPS), Price Earning Ratio (PER) and Price to Book Value (PBV) of the retail company listed on the Indonesia Stock Exchange. Total population of these study was 22 companies and after passing through purposive sampling then it is obtained a total sample of 14 companies. The analysis technique used in this research is multiple linear regression to obtain a picture of the overall relationship between the variables. Based on the multiple linear regression analysis, t test research results show that the variable inflation has negative relation and not significant effect to the stock price. The variable interest rate  has positive  relation and not significant effect to the stock price. Variable earnings per share, price earnings ratio and price to book value have positive relation and significant effect to the stock price. Determination of test results showed that the variable inflation, interest rates, earnings per share, price earnings ratio and price-to-book value capable of influencing the sretail company’s stock price by 59% while the remaining 41% is influenced by other factors outside the research model. Keywords: inflation, interest rates, earnings per share, the price-to-earnings ratio and price to book value.